PERAN MOTIVASI KERJA DALAM MEMEDIASI KOMPENSASI DAN KINERJA PEGAWAI - Realita, Tasnim Nikmatullah (Magister Manajemen Universitas Wisnuwardhana, 2021)
It is important to know the role of work motivation as a mediator of the influence of remuneration on the performance of the Malang Family Population Planning and Control Department, as the population in Malang area is the main task of planning and serving the community. The purpose of this study is to analyze the direct influence of remuneration and motivation on work results and the mediating role of motivational variables is the influence of remuneration on the work results of employees of the Department. Population Control and Family Planning in Malang Regency. The sample for this study included employees of the Malang Department of Population Control and Family Planning with a total of 63 employees. This study uses path analysis. The results of the study explain that there is a direct influence of compensation and motivation on employee performance. This dynamic can minimize the impact of compensation on the performance of the Bureau of Population Control and Family Planning staff in Malang Regency.